(3QSGdI aj eYQaI GdbSi GdadcjI HYVgG ef HYV HWQjb ZjQ WQjb eYQaJgG HGdTcd GdbWGY hGdfSHI GdeDdaIs - (3efUhQ Hf Ydj, CHh fUQ GHf YQGb , J fMh (B425 (3g`s
(3ChdgG (B:s
(3PcQJ CjOc Gddg Edi ef jMQU Ydi Yde GdgjFI hjMH Gdhbha Ydi HQGgjf eG JVefg GdGRjGL ef afhf GdMSGHGJ GdeJTYHI s
(3BNQgG (B:s
(3ai GdGHhGH GdJi jTJed YdjgG Yf JWhjd ZjQi hGSJYfJ Hg ai SGFQ eG jTGA cdg ef eSGFd GdeMOKjf Ef jTGA Gddg JeJ GdQSGdI hGdMeO ddg ceG gh Cgdg hUdhGJg Ydi fHjg eMeO hGdg GdWGgQjf s
(3HYK HgG GdeDda Edi CHj GdQjMGf GdHjQhfis
(3HgG CTcGd hQShe gfOSjIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdadcs